Minuman fungsional torbangun (Coleus amboinicus Lour) dapat menurunkan tingkat keluhan dan kadar prostaglandin pada remaja dengan sindrom pramenstruasi - Novaria, Astri Ayu; Hardinsyah, Hardinsyah; Damanik, Muhammad Rizal Martua (Jurnal Gizi dan Pangan, 2017)
This study aimed to analyze the effect of torbangun functional drink on the premenstrual syndrom (PMS) symptoms and the levels of prostaglandin in adolescents. Amount of 12 adolescents in this study were devided into two groups through the inclusion and exclusion criterias. The result of Wilcoxon test showed the mean decreasion on the level of complaints of torbangun functional drink group (p<0.05), whereas the control group did not experience significant decreasing on the level of complaints. Meanwhile, the result of paired t-test of torbangun functional drink group experienced significant decline (p=0.01) of prostaglandin level (580.6±227.9) pg/dl while compared to the control group which did not show significant decline (p<0.05) of prostaglandin level (300.3±273.9)pg/dl. The result of the independent t-test test showed that the delta value of prostaglandin level were significantly different (p=0.01) before and after intervention between two groups. All in all, torbangun functional drink could be an alternative to reduce the symptoms of PMS and prostaglandin levels.